ANALISIS DAMPAK TURBULENSI TEKNOLOGI TERHADAP HUBUNGAN ANTARA KECAKAPAN DALAM E-COMMERCE DAN KUALITAS INFORMASI AKUNTANSI - , DIAN AULIAWATI PURNAMA, Dr. Sumiyana, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study examines the effect of e-commerce competence on accounting information quality with technological turbulence as a moderator. The competence of e-commerce covers effective database management, sufficient financial supervision, and optimizing inventory control. This study also uses accounting staff in e-commerce firm as object of the research. Questionnaire is the method that is used in this research. The result indicates that e-commerce competences have positive direct effect on accounting information quality. This research shows effective database management, sufficient financial supervision, and optimizing inventory control have positive influence on accounting information quality under technological turbulence.